2002
DOI: 10.1007/s00066-002-0985-9
|View full text |Cite
|
Sign up to set email alerts
|

Bevölkerungsbezogene Studie über die Anwendung adjuvanter Strahlentherapie bei Patientinnen mit Mammakarzinom

Abstract: Following BCT compliance with treatment recommendations regarding radiation therapy was high. Women in older age or with comorbidities received less often radiation therapy. Subsequent to mastectomy indicators for the use of radiation therapy were identified. Among clinics differences in the adherence to treatment recommendations were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 22 publications
1
7
0
2
Order By: Relevance
“…Several trials were performed lasting several years, and in parallel, thousands of patients were treated according to the "expected results" outside of these trials. Up to 30% of the patients in the respective age group did not receive the proper treatment [10]. However, in none of these prospective trials any subgroup could be identified which did not benefit from WBRT in terms of a reduced rate of IBTR in all age and risk groups.…”
mentioning
confidence: 99%
“…Several trials were performed lasting several years, and in parallel, thousands of patients were treated according to the "expected results" outside of these trials. Up to 30% of the patients in the respective age group did not receive the proper treatment [10]. However, in none of these prospective trials any subgroup could be identified which did not benefit from WBRT in terms of a reduced rate of IBTR in all age and risk groups.…”
mentioning
confidence: 99%
“…Longitudinally only 1.1% of the women complained at measurement point t6 moderate stress (grade 2) in the course of radiotherapy. Nagel and coworkers [22] confirmed in a field study with breast cancer patients a high rate of adjuvant radiotherapy in addition to breast-conserving surgery of 90.6%. The study documented a very impressive high level of acceptance of adjuvant radiotherapy after breast-conserving surgical care which was in concordance with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Nagel und Mitarbeiter [7] stellten vor knapp einem Jahrzehnt bei der Gruppe von über 70-Jährigen eine Unterversorgung mit Radiotherapie fest. Das betreffe 30% der über 70-Jährigen im Vergleich zu nur 3-5% der jüngeren Patientinnen.…”
Section: Kommentarunclassified